Hubungan Personal Hygiene dengan Kejadian Penyakit Dermatitis di UPTD Puskesmas Kawatuna - Hikmah Wati; Tigor H. Situmorang; Matius Paundanan; Usy Nora Manurung (KEWINUS: Jurnal Keperawatan dan Kesehatan, 2025)
Dermatitis is a non-inflammatory-inflamatory skin disease that can affect the epidermis and dermis layers both immmediately and over a long period of time. Infections, digestive system diseases, dental health problems, and skin diseases can be caused by poor personal hygiene. The aim of this study was to determine the relationship between personal hygiene and the incidence of dermatitis at the UPTD of the Kawatuna Community Health Center. This research uses a cross sectional design and quantitativee methodology. The research population consisted dermatitis sufferers who received treatment at the UPTD Kawatuna Community Health Center from March to May 2024. Of this number, the sample consisted of 37 respondents. Spearman statistical test was used to analyze incidental sampling. Personal hygiene and the prevalence of dermatitis at the Kawatuna Public Health Center uptd have a significant relationship, based on data collected from 37 respondents. The spearman rank test obtained a p value of 0,007 <0,05. This shows that there is a statistically significant relationship between the incidence of dermatitis and personal hygiene. There is a correlation between personal hygiene and the incidence of dermatitis at Kawatuna Public Health Center. This is expected to increase public awareness of the need to protect themselves and their surrounding environment to prevent dermatitis   Keywords: Dermatitis; Disease;  Personal Hygiene